Deficiency of Integrin β4 Results in Increased Lung Tissue Stiffness and Responds to Substrate Stiffness via Modulating RhoA Activity - Chi, Yinxiu; Chen, Yu; Jiang, Wang; Huang, Wenjie; Ouyang, Mingxing; Liu, Lei; Pan, Yan; Li, Jingjing; Qu, Xiangping; Liu, Huijun; Liu, Chi; Deng, Linhong; et al. (Frontiers in Cell and Developmental Biology, 2022)
The interaction between extracellular matrix (ECM) and epithelial cells plays a key role in lung development. Our studies found that mice with conditional integrin β4 (ITGB4) knockout presented lung dysplasia and increased stiffness of lung tissues. In accordance with our previous studies regarding the functions of ITGB4 in bronchial epithelial cells (BECs), we hypothesize that the decreased ITGB4 expression during embryonic stage leads to abnormal ECM remodeling and increased tissue stiffness, thus impairing BECs motility and compromising lung development. In this study, we examined lung tissue stiffness in normal and ITGB4 deficiency mice using Atomic Force Microscopy (AFM), and demonstrated that ITGB4 deficiency resulted in increased lung tissue stiffness. The examination of ECM components collagen, elastin, and lysyl oxidase (LOX) family showed that the expression of type VI collagen, elastin and LOXL4 were significantly elevated in the ITGB4-deficiency mice, compared with those in normal groups. Airway epithelial cell migration and proliferation capacities on normal and stiff substrates were evaluated through video-microscopy and flow cytometry. The morphology of the cytoskeleton was detected by laser confocal microscopy, and RhoA activities were determined by fluorescence resonance energy transfer (FRET) microscopy. The results showed that migration and proliferation of ITGB4 deficiency cells were noticeably inhibited, along decreased cytoskeleton stabilization, and hampered RhoA activity, especially for cells cultured on the stiff substrate. These results suggest that decreased ITGB4 expression results in increased lung tissue stiffness and impairs the adaptation of bronchial epithelial cells to substrate stiffness, which may be related to the occurrence of broncho pulmonary dysplasia.